Das Herrscherlob als Beispiel für die Gelegenheitslyrik des ausgehenden 19. Jhs. in der Provinz Posen - Wojtczak, Maria (Studia Germanica Posnaniensia, 2018)
In the years 1871-1918, on the territory of the Duchy of Poznan, there were published over 90 magazines and newspapers. Apart from the current articles also German prose and poetry were printed and they are the point of this article. 80% of poetry published in this press is so called „Heimatdichtung“, the rest is war lyric poetry, including poems worshipping then leaders and rulers of Germany. The typical feature for these poems is the false reality of literary communication which, in a way, reflects the „false historical reality“, that is the German presence in the Duchy of Poznan in 19th century.